Conflict-related violence against women: transforming transition - Swaine, Aisling (Cambridge University Press, 2018)
"By comparatively assessing violence against women in three conflict-affected jurisdictions (Liberia, Northern Ireland and Timor-Leste), Conflict Related Violence Against Women empirically and theoretically expands current understanding of the form and nature of conflict- related violence against women. Employing a disaggregated and aggregated approach, the book first documents violence against women in each context's pre-, mid- and post-conflict phase, and then assesses the relations between the violence in each phase on an aggregated basis"--